NETWORKS AND INTERMEDIARIES IN SEASONAL AGRICULTURAL LABOR MARKETS IN TURKEY - Motoi Kusadokoro; Takeshi Maru; Ufuk Gültekin (International Journal of Food and Agricultural Economics, 2016)
In casual labor markets, intermediaries are used in order to match employers and employees. This function is especially important when the market is imperfect and employers and employees have not formed solid networks. This paper investigates the network effects and the role of intermediaries in the seasonal agricultural labor market in the irrigated area of Adana, Turkey. The network of rural households is divided into one composed mainly of farmers and one composed mainly of seasonal agricultural workers. Our regression analyses show that the seasonal workers who do not have strong networks with farmers have difficulty finding jobs. Middlemen serve to mitigate the seasonal workers’ lack of a network and play a key role in the area’s seasonal agricultural labor market. At the same time, however, blood ties and territorial ties between middlemen and workers may cause middlemen to discriminate among seasonal workers based on their origins.